Phytochemical investigation of Erythropalum scandens Blume stems: Discovery of erythropalumins A–J and mechanistic insights into the traditional ‘clear-heat’ effects - Quoc-Dung Tran Huynh; Thuy-Tien Thi Phan; Sui-Wen Hsiao; Man-Hsiu Chu; Yun-Han Wang; Ngoc-Thac Pham; Huong-Giang Le; Phuong Vu Luu; Truc-Ly Thi Duong; Dang-Khoa Nguyen; Bien-Thuy Bui Nguyen; Thanh-Hoa Vo; et al. (Phytochemistry, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Development of a pomelo pectin–based microencapsulation system for Akkermansia muciniphila - Chang-Han Wang; Wen-Yu Liu; She-Ching Wu (Food Chemistry, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Development of ccombodies identify WSSV VP28 protein - Sung Ok Shin; Rodelas-Angelia Abigail Joy; Angelia Mark Rickar; Han-Ching Wang; Seung Beom Hong; Tae Sung Jung (Fish & Shellfish Immunology, 2025)

Multifunctional roles of WSSV079 and WSSV164 in RNA regulatory networks during WSSV replication in Litopenaeus vannamei - Brandon Rafael de Jesús Castillo-Corea; Shih-Shun Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Perilla leaf extract as a functional feed additive enhances immunity and AHPND resilience in shrimp - Athiya Azzahidah; Ramya Kumar; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Host acetyl-CoA pathways support WSSV replication - Shu-Wen Cheng; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Genome characterization and pathogenesis of translucent post-larvae disease in white shrimp - Ramya Kumar; Athiya Azzahidah; Yik How Teoh; Chu-Fang Lo; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

WSSV regulates malate-aspartate shuttle during infection - Yen Siong Ng; Fang-Jyun Guo; Kuan-Lun Huang; Cong-Yan Chen; Shu-Wen Cheng; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Deciphering the mechanism behind shrimp body color regulation - Yun Chen; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Mitochondrial pyruvate carrier proteins mediate host-pathogen interactions during WSSV infection in shrimp - Yu-Chen Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Reframing the understanding of WSSV pathogenesis via multi-omics dissection of host control - Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Development of a marine probiotic bacterium producing nanobody and/or dsRNA against white spot syndrome virus (WSSV) - Mary Nia M. Santos; Fernand Fagutao; See-Yeun Ting; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Foreword to “The 5th conference of the international society of fish and shellfish immunology (5th ISFSI) in Tainan, Taiwan (R.O.C.) (November 4th – 8th, 2025)” - Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Anti-inflammatory glycosides from Gomphandra mollis Merr.: Structural elucidation and mechanistic insights - Quoc-Dung Tran Huynh; Thuy-Tien Thi Phan; Man-Hsiu Chu; Thanh-Vu Nguyen; Truc-Ly Thi Duong; Su-Jung Hsu; Yun-Han Wang; Ngoc-Thac Pham; Bien-Thuy Nguyen Bui; Dang-Khoa Nguyen; Thanh-Hoa Vo; Ta-Wei Liu; et al. (Phytochemistry, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Bile acid- and taurocholate-mediated virulence in AHPND-causing Vibrio parahaemolyticus is independent of the LuxO-OpaR quorum sensing cascade - Ramya Kumar; Shin-Jen Lin; Chien-Kang Huang; Shih-Shun Lin; Hao-Ching Wang; Fernand F. Fagutao; Han-Ching Wang (Aquaculture, 2025)

Singular value decomposition of near-field electromagnetic data for compressing and accelerating deep neural networks in the prediction of geometric parameters for through silicon via array - Song-En Chen; Eugene Su; Chih-Chung Wang; Jia-Han Li; Chao-Ching Ho (Computer Physics Communications, 2025)

ARRDC3, a novel α-arrestin, modulates WSSV replication and AHPND pathogenesis in Litopeneaus vannamei - Ramya Kumar; Brandon Rafael de Jesús Castillo-Corea; Shih-Shun Lin; Chien-Kang Huang; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Dynamic changes in the metabolome and microbiome during Citrus depressa Hayata liquid fermentation - Ta-Wei Liu; Benni Iskandar; Man-Hsiu Chu; Yun-Han Wang; Ting-An Huang; Su-Jung Hsu; Yves S.Y. Hsieh; Ching-Kuo Lee (Food Chemistry, 2025)

Zeolite 13X particles with porous TiO2 coating and Ag2O nanoparticles as multi-functional filler materials for face masks - Wei Su; Kaiying Wang; Han Yu; Fateme Fayyazbakhsh; Jeremy Watts; Yue-Wern Huang; Jee-Ching Wang; Xinhua Liang (Chemical Engineering Journal, 2024)

Introduction to the Special Issue: Microbiome and its impact on immunity in fish and shrimp - Han-Ching Wang; Hsiao-Pei Lu (Fish & Shellfish Immunology, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Resilience and probiotic interventions to prevent and recover from shrimp gut dysbiosis - Ramya Kumar; Mei-Ying Huang; Chih-Ling Chen; Han-Ching Wang; Hsiao-Pei Lu (Fish & Shellfish Immunology, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

The regulation of shrimp metabolism by the white spot syndrome virus (WSSV) - Ramya Kumar; Jiun‐Yan Huang; Yen‐Siong Ng; Cong‐Yan Chen; Han‐Ching Wang (Reviews in Aquaculture, 2022)
For more than three decades, infectious diseases have been one of the major causes of economic losses in the global shrimp industry. One of the deadliest of the shrimp pathogens is white spot syndrome virus (WSSV), which causes mass mortality in farmed shrimp. Various aspects of WSSV pathogenicity have been studied, but in this review, we will focus only on one of them, namely metabolic reprogramming. WSSV’s modulation of host metabolism affects glycolysis, the tricarboxylic acid (TCA) cycle, glutaminolysis and lipid metabolism. Several signaling pathways are involved in this regulation, including JAK‐STAT, PI3K‐AKT‐mTOR, MAPK and Ras‐Raf‐MEK, with the PI3K‐Akt‐mTOR pathway in particular playing a critical role in activating the WSSV‐induced Warburg effect. Taken together, these changes benefit the virus by facilitating WSSV replication. In this review, we summarize current knowledge regarding the metabolism‐related aspects of WSSV pathogenesis, and discuss the mechanisms by which this virus reprograms its host's metabolic pathways. A deeper understanding of these pathways, key metabolic enzymes and signaling mechanisms is potentially important for the development of effective anti‐WSSV strategies.

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

Acute hepatopancreatic necrosis disease in penaeid shrimp - Ramya Kumar; Tze Hann Ng; Han‐Ching Wang (Reviews in Aquaculture, 2020)
Asian countries are the major producers of cultured Penaeid shrimps such as Penaeus monodon and Penaeus ( Litopenaeus ) vannamei . In recent years, shrimp production has declined due to the emergence of a bacterial disease called acute hepatopancreatic necrosis disease (AHPND). This disease is mainly caused by Vibrio parahaemolyticus , but other Vibrio species are also known to cause AHPND in shrimps. Here, in addition to reviewing recent developments in the field of AHPND diagnosis, host responses to AHPND, the role of microbiota during AHPND infection and the current treatment options for AHPND, we also describe a model of AHPND pathogenesis.

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Microarray Analyses of Shrimp Immune Responses - Takashi Aoki; Han-Ching Wang; Sasimanas Unajak; Mudjekeewis D. Santos; Hidehiro Kondo; Ikuo Hirono (Marine Biotechnology, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Sequencing and Amplified Restriction Fragment Length Polymorphism Analysis of Ribonucleotide Reductase Large Subunit Gene of the White Spot Syndrome Virus in Blue Crab (Callinectes sapidus) from American Coastal Waters - Yun-Shiang Chang; Shao-En Peng; Han-Ching Wang; Hui-Chen Hsu; Ching-Hui Ho; Chung-Hsiung Wang; Sho-Ya Wang; Chu-Fang Lo; Guang-Hsiung Kou (Marine Biotechnology, 2001)